Developing an aging facial skin quality scoring system for Taiwanese females: A comparative study - Tzu-Miao Lin; Hsi-Chieh Lee; Kuang-Hung Hsu (International Journal of Management, Economics and Social Sciences (IJMESS), 2017)
This study aims to develop a standardized skin testing procedure to identify facial skin biophysical properties and impact factors of females in Taiwan by using the epidemiology investigation method of a cross-sectional study for facial skin quality. A total of 389 female volunteers aged 18-70 years from across Taiwan and with apparent healthy facial skin took part in the study. Seven facial skin biophysical properties were taken in a controlled environment and using a standardized protocol to ensure consistency of survey. The relationship between facial skin biophysical properties and chronological age were found to follow a linear model; as expected the properties were found to decline with age. Certain lifestyle habits known to have significant effects on facial skin aging were identified. They include body mass index, menstrual cycle, menopausal status, onset of menopause, lifetime sun exposure, hair dye usage, routine of facial cleansing, methods of daily skin care, skin color, skin type and geographical location. A Facial Skin Quality Aging Score System was developed, and it was discovered that the calculated scores significantly (p<0.0001) increased with chronological age. The facial skin surface sebum casual level exhibited a distinguishably biphasic decrease (p<0.0018), with a sharp drop between the chronological age groups of 35-39 and 40-44. In conclusion, our study demonstrated that a standardized Facial Skin Quality Aging Score System could be used for producing a global systematic reference for human skin quality aging. A standardized facial skin testing center, testing procedure and prediction index of skin quality aging for the Taiwanese population are important concerns. The results of this study could be helpful to the consideration of proper measures for dermatology and cosmetic products.
Keywords: 330; Skin aging; skin biophysical properties; photo images of facial skin; facial skin quality aging score system; courage+khazaka cutometer MPA580